Screening children with neurofibromatosis type 1 for autism spectrum disorder. Issue 7 (8th April 2014) - Tinker, Jade; Carbone, Paul S.; Viskochil, David; Mathiesen, Amber; Ma, Khe‐Ni; Stevenson, David A.
<x xml:space="preserve">Abstract</x> Autism spectrum disorder (ASD) is reported to be increased in neurofibromatosis type 1 (NF1), but it's unknown if ASD screening tools are sensitive and specific for NF1. This study compared the rate at which children with NF1 screen‐positive for two ASD screening tools [Modified Checklist for Autism in Toddlers (M‐CHAT) and Childhood Autism Spectrum Test (CAST)] to the screen‐positive rate of the general population. A retrospective cross‐sectional observational design to investigate the association between children with NF1 and at risk status for ASD was used. Medical records of children between 16 months and 11 years of age seen in an NF Clinic were reviewed for an ASD screening questionnaire. There were no statistically significant differences in the screen‐positive rate for ASD in NF1 compared to published controls, but mean CAST scores were higher in NF1. © 2014 Wiley Periodicals, Inc.